2023
DOI: 10.3389/fimmu.2023.1134020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological spectra of human cutaneous leishmaniasis in North Africa and French Guiana

Abstract: Cutaneous leishmaniasis (CL) caused by infection with the parasite Leishmania exhibits a large spectrum of clinical manifestations ranging from single healing to severe chronic lesions with the manifestation of resistance or not to treatment. Depending on the specie and multiple environmental parameters, the evolution of lesions is determined by a complex interaction between parasite factors and the early immune responses triggered, including innate and adaptive mechanisms. Moreover, lesion resolution requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…This particular parasitic infection, which exhibits a variety of clinical manifestations, is caused by different species of the Leishmania genus, resulting in complications that range from small skin ulcers to potentially fatal systemic damage to vital organs such as the bone marrow, liver, and spleen [ 2 ]. Leishmaniasis is prevalent in over 100 countries, affecting approximately 350 million individuals, with 12 million of them being infected, primarily in tropical and subtropical regions, particularly in Africa [ 3 , 4 ]. Thus, the impact of leishmaniasis on this continent is significant, often impacting vulnerable populations and being exacerbated by numerous risk factors, deficiencies in diagnostic approaches, and the absence of effective treatments [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This particular parasitic infection, which exhibits a variety of clinical manifestations, is caused by different species of the Leishmania genus, resulting in complications that range from small skin ulcers to potentially fatal systemic damage to vital organs such as the bone marrow, liver, and spleen [ 2 ]. Leishmaniasis is prevalent in over 100 countries, affecting approximately 350 million individuals, with 12 million of them being infected, primarily in tropical and subtropical regions, particularly in Africa [ 3 , 4 ]. Thus, the impact of leishmaniasis on this continent is significant, often impacting vulnerable populations and being exacerbated by numerous risk factors, deficiencies in diagnostic approaches, and the absence of effective treatments [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In leishmaniasis, both innate and adaptive immune responses are indistinguishably associated together as the cytokines generated by cells of the innate system control the result and extent of the adaptive immunity [ 11 ]. Therefore, the evoked immune responses are necessary to be firmly regulated to evade immune-mediated damage in host tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Non-responsive skin lesions in mice are linked with a few TCD4+ [ 14 ]. A report indicated that local immune limits, such as cellular and cytokines liberated in the lesion, control organisms and protect against the pathological process [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although cutaneous lesions caused by the different Leishmania species are similar, the pathogenesis may be quite different. While parasites are found in large numbers in the lesions caused by L. guyanensis , L. mexicana , L. major , and L. tropica , parasites are scarce in tegumentary leishmaniasis caused by L. braziliensis [ 2 , 3 , 4 , 5 ]. Moreover, while L. tropica , L. major , L. peruviana , L. panamensis , and L. mexicana cause only CL, L. braziliensis , L. amazonensis , and L. guyanensis may cause CL, mucosal leishmaniasis (ML), and disseminated leishmaniasis (DL).…”
Section: Introductionmentioning
confidence: 99%